YURIDIKSI PENEGAKAN HUKUM TERHADAP TINDAK PIDANA RADIKALISME DI INDONESIA - Siswahyulianto, Heri; Andy Usmina Wijaya (JATISWARA, 2026)
Radicalism in Indonesia has evolved from merely an ideological perspective into a tangible threat to national stability, particularly in line with the digital transformation that accelerates the spread of propaganda and online recruitment. This situation creates a need for legal clarity regarding the jurisdiction and authority of authorities in handling pre-terror actions, such as the dissemination of extremist teachings, digital financing, and ideological training without physical violence. The revision of Law Number 5 of 2018 concerning the Eradication of Terrorism Crimes expands the authority of officials by emphasizing a preventive approach, yet it presents challenges in balancing national security with the protection of human rights. This study employs a normative legal method with statutory and conceptual approaches to analyze the effectiveness of jurisdictional regulations in countering radicalism, as well as to assess the synergy among law enforcement agencies such as the Indonesian National Police, Densus 88, the National Counter Terrorism Agency (BNPT), and the Prosecutor's Office. The research results indicate that although the national legal system has been relatively comprehensive, overlaps in authority and weak coordination among agencies are still evident, potentially reducing the effectiveness of law enforcement. Therefore, the strengthening of law enforcement jurisdiction should be directed towards regulatory harmonization, the establishment of inter-agency coordination forums, and the enhancement of institutional transparency and accountability. Legal system reform based on institutional collaboration and the reinforcement of human rights principles constitutes a strategic step in building a jurisdictional system that is adaptive to modern radicalism threats.